Techno-Economic Assessment of Hybrid Renewable Micro Grids for Sustainable Rural Electrification - Golam Rabbany; Swarup Kumar; Uniwan-E-mi Dhar; Md Shoriful Islam; Md Tousiat Sarker (Peneliti Teknologi Teknik Indonesia, 2026)
This paper presents a stochastic and climate-informed techno-economic optimization framework for the optimal design of off-grid hybrid renewable energy micro grids aimed at sustainable rural electrification. The proposed system integrates solar photovoltaic (PV) generation, wind turbines, battery energy storage systems (BESS), and a diesel generator as backup to ensure reliable electricity supply under uncertain demand and variable renewable resources. Monte Carlo–based stochastic load modeling and climate-adjusted renewable resource assessment are employed to capture site-specific operating conditions. System sizing and operation are optimized using a multi-objective cost minimization approach targeting the Levelized Cost of Energy (LCOE) and Net Present Cost (NPC), subject to predefined reliability and operational constraints, including a Loss of Power Supply Probability (LPSP ≤ 5%). Simulation results demonstrate that the optimized hybrid microgrid configuration reduces the LCOE by approximately 18–25% and diesel fuel consumption by over 40% compared to conventional deterministic designs, while achieving a renewable energy penetration exceeding 85%. In addition, the proposed framework leads to an estimated reduction in CO₂ emissions of about 45%, enhancing long-term environmental sustainability. These findings confirm that incorporating stochastic demand representation and climate-aware resource evaluation significantly improves the economic viability, reliability, and affordability of hybrid renewable microgrids for electrifying remote rural communities.